Proxy measures of vitamin D status – season and latitude – correlate with adverse outcomes after bariatric surgery in the Nationwide Inpatient Sample, 2001–2010: a retrospective cohort study. (14th December 2015) - Peterson, L. A.; Canner, J. K.; Cheskin, L. J.; Prokopowicz, G. P.; Schweitzer, M. A.; Magnuson, T. H.; Steele, K. E.
Summary: Objective: To investigate the association between adverse surgical outcomes following bariatric surgery and proxy measures of vitamin D (VitD) status (season and latitude) in the Nationwide Inpatient Sample (NIS). Background: Obesity is an independent risk factor for VitD deficiency (25(OH)D < 20 ng ml −1 ). VitD deficiency compounds the chronic inflammation of obesity, increasing the risk of adverse outcomes following bariatric surgery. Epidemiology has long used season and latitude as proxies for group VitD, as VitD status is largely determined by sun exposure, which is greatest during summer and at the Equator. Methods: We assessed proxy measures of group VitD status. We compared surgeries in VitD Summer (July to September), Winter (January to March), and Fall/Spring (October to December and April to June) and in the North (≥37°N) vs. the South (<37°N). Results: We identified 932, 091 bariatric surgeries; 81.2% were women and 74.4% were white. Sex was unequally distributed by season ( p = 0.005). Median age was 43.0 years (all groups). Most surgeries occurred in the North (64.8%). Adverse outcome rates ranged from 0.01% (wound infections) to 39.4% [prolonged length of stay LOS]. Season was inversely associated with wound infection ( p = 0.018) and dehiscence ( p = 0.001). Extended LOS was inversely correlated with season ( p < 0.001). These relationships held after adjustment. Prolonged LOS ( p < 0.001) and any complication ( p = 0.108) were more common in the North. Conclusions: We have demonstrated a graded relationship between seasonality and adverse outcomes following bariatric surgery. The association was strongest for dehiscence and prolonged LOS. These relationships held when using latitude. A prospective study measuring pre‐operative 25(OH)D concentration would strengthen the case for causality in adverse surgical outcomes.